Participation of endotoxin in root canal infections: A systematic review and meta-analysis - Martinho, Frederico Canato; de Rabello, Diego Guilherme Dias; Ferreira, Luciana Louzada; Nascimento, Gustavo Giacomelli (Thieme, 2017)
This systematic review and meta-analysis aimed to evaluate the relationship between endotoxin levels and presence of clinical signs/symptoms and radiographic features in patients with endodontic infection. Electronic searches were performed on Medline/ PubMed, Embase, Cochrane Library, Scielo, Science Direct, Web of Knowledge and Scopus databases for identification of relevant studies published up to December 2016. Grey literature was searched in Google Scholar. The selected literature was reviewed independently by two authors. Clinical studies evaluating the levels of endotoxin and the presence of clinical and radiographic features were included in this review. In order to determine the relationship between endotoxin levels and presence of clinical signs/symptoms and radiographic features meta-analyses were performed. Among the 385 articles identified in the initial search, 30 were included for full-text appraisal and only eight studies met the inclusion criteria for this systematic review. Meta-analysis revealed that individuals having teeth with tenderness to percussion (TTP) (P = 0.04; I2 57%) and previous episode of pain (PEP) (P = 0.001; I2 81%) had higher levels of endotoxin than their counterparts. Size of radiographic lesion > 2 mm (P = 0.02; I2 68%) and presence of root canal exudation (EX) (P = 0.0007; I2 0%) were associated with higher levels of endotoxin. This systematic review and meta-analyses provided a strong evidence that endotoxin are related with the presence of clinical signs/symptoms and radiographic features in patients with endodontic infection.
Keywords: Endodontic treatment; Endotoxins; Meta-analysis; Systematic review